Redescription of Ololaelaps tasmanicus (Womersley, 1956) and description of a new species of Ololaelaps Berlese (Acari: Laelapidae) from Iran - Babaeian, Esmaeil; Ghobari, Hamed; Samani, Kyumars Mohammadi (Zootaxa, 2019)
Ololaelaps tasmanicus (Womersley, 1956) is redescribed from the holotype female and two additional female specimens from Australia. Ololaelaps elongatus Babaeian sp. nov. is described and illustrated from specimens from soil in Western Iran. The new species can be distinguished from the other congeners by four diagnostic morphological character states: (1) dorsal shield setae moderately long; (2) sternal shield elongate, almost reaching to level of mid-coxa IV, and fused with endopodals III–IV posterolaterally; (3) peritrematal shield posteriorly fused to exopodal shields IV, and free from genitiventrianal shield; (4) genitiventrianal shield with four pairs of pre-anal setae, Zv2 and Jv3 off shield. Additional notes on the holotype of Ololaelaps obovata (Womersley, 1960) and a key to the identification of species of Ololaelaps occurring in Iran are also presented. O. paratasmanicus Ryke, 1962 is considered as junior synonym of O. tasmanicus.